Urine metabolomics in rats after administration of ketamine - Wen, Congcong (Drug Des Devel Ther, 2015)
In this study, we developed a urine metabonomic method, based on gas chromatography–mass spectrometry (GC-MS), to evaluate the effect of ketamine on rats. Pattern recognition analysis, including both principal component analysis and partial least squares discriminate analysis revealed that ketamine (50 mg/kg) induced metabolic perturbations. Compared with the control group, at day 7, the level of alanine, butanoic acid, glutamine, butanedioic, trimethylsiloxy, L-aspartic acid, D-glucose, cholesterol, acetamide, and oleic acid of the ketamine group was increased, while the level of 2,3,4-trihydroxybutyric acid, benzeneacetic acid, threitol, ribitol, xylitol, and glycine decreased. At day 14, the level of alanine, ethanedioic acid, L-proline, glycerol, tetradecanoic acid, l-serine, l-phenylalanine, L-aspartic acid, d-glucose, cholesterol, heptadecanoic acid, and acetamide in rat urine of the ketamine group was increased, while the 2,3,4-trihydroxybutyric acid, benzeneacetic acid, d-ribose, threitol, ribitol, glycine, pyrazine, and oleic acid levels decreased. Our results indicate that metabonomic methods based on GC-MS may be useful to elucidate ketamine abuse, through the exploration of biomarkers.